ANALISIS PENGARUH KUALITAS WEBSITE DUMAS PRESISI PENGADUAN MASYARAKAT TERHADAP KINERJA ANGGOTA POLRI DI WILAYAH HUKUM POLRES KEEROM POLDA PAPUA - Ryan Aditya; Emy L. Tatuhey (ADISAM PUBLISHER, 2025)
This study aims to analyze the influence of the quality of the Dumas Presisi public complaint website on the performance of police officers within the jurisdiction of Polres Keerom, using the End User Computing Satisfaction (EUCS) model. The research evaluates five core EUCS dimensions: content, accuracy, format, ease of use, and timeliness. A total of 92 community members and 26 police staff were selected as respondents through simple random sampling. Data were collected via questionnaires and analyzed using validity and reliability tests, as well as multiple linear regression. The results indicate that all EUCS dimensions significantly affect user satisfaction, with ease of use having the greatest impact (β = 0.362). Although content received the highest satisfaction score, timeliness was identified as the weakest aspect. Recommendations include enhancing the user interface, improving system speed and data accuracy, and providing regular training and system audits. These findings are expected to serve as a reference for improving digital public complaint services within the Indonesian National Police